Intercomparison measurements of two 33S-enriched sulfur isotope standards. Issue 6 (18th March 2019) - Geng, L.; Savarino, J.; Caillon, N.; Gautier, E.; Farquhar, J.; Dottin III, J. W.; Magalhães, N.; Hattori, S.; Ishino, S.; Yoshida, N.; Albarède, F.; Albalat, E.; et al.
Abstract : Isotopic compositions of two S-33 enriched sulfur standards were assessed for the normalization of Δ 33 S and Δ 36 S data, to fulfill the need of accurate message extraction from S-MIF signals in atmospheric and geological samples. Abstract : Despite widespread applications of sulfur isotope mass-independent fractionation (MIF) signals for probing terrestrial and extra-terrestrial environments, there has been no international sulfur isotope reference material available for normalization of Δ 33 S and Δ 36 S data. International reference materials to anchor isotope values are useful for interlaboratory data comparisons and are needed to evaluate, e.g., whether issues exist associated with blanks and mass spectrometry when using different analytical approaches. We synthesized two sodium sulfate samples enriched in 33 S with different magnitudes, and termed them S-MIF-1 and S-MIF-2, respectively. The sulfur isotopic compositions of these two samples were measured in five different laboratories using two distinct techniques to place them on the V-CDT scale for δ 34 S and a provisional V-CDT scale for Δ 33 S and Δ 36 S. We obtained average δ 34 S values of S-MIF-1 = 10.26 ± 0.22‰ and S-MIF-2 = 21.53 ± 0.26‰ (1 σ, versus V-CDT). The average Δ 33 S and Δ 36 S values of S-MIF-1 were determined to be 9.54 ± 0.09‰ and −0.11 ± 0.25‰, respectively, while the average Δ 33 S and Δ 36 S values of S-MIF-2 are 11.39 ± 0.08‰ and −0.33 ± 0.13‰ (1 σ, versus V-CDT). The lack of variation among the interlaboratory isotopic values suggests sufficient homogeneity of S-MIF-1 and S-MIF-2, especially for Δ 33 S. Although additional measurements may be needed to ensure the accuracy of the isotopic compositions of S-MIF-1 and S-MIF-2, they can serve as working standards for routine Δ 33 S analysis to improve data consistency, and have the potential to serve as secondary sulfur isotope reference materials to address issues such as scale contraction/expansion and for normalization and reporting of Δ 33 S and Δ 36 S between laboratories. For the same reasons as listed for sulfur isotopes, the same standards were also artificially enriched in 17 O. The calibration is still in progress but first estimations gave Δ 17 O = 3.3 ± 0.3‰ with unassigned δ 18 O.